Insider-outsider adult learners: Culture and the meaning-making of belonging in graduate education​ - McClurg, Caitlin (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2025)
With competing interests on time and resources, adult learners in formal education often hold “both-and” identity constructs when describing themselves as students, especially considering the multiplicity of their lives in the workplace, and at home. Drawing on concepts and discourses related to Bourdieu’s habitus, field, and culture, this presentation will engage in a reflexive discussion that considers positionality and belonging. Belonging is a personal journey of feeling like an outsider, insider, both-and simultaneously. This paper invites readers to consider their positionality as both insiders and outsiders, as well as their sense of belonging in academia. This conference paper reflects the content of the July 2024 Tapestries of Learning oral conference presentation and is part of the Tapestries of Learning Conference Proceedings.